2011
DOI: 10.1007/s10592-011-0195-z
|View full text |Cite
|
Sign up to set email alerts
|

High connectivity among argali sheep from Afghanistan and adjacent countries: Inferences from neutral and candidate gene microsatellites

Abstract: We quantified population connectivity and genetic variation in the Marco Polo subspecies of argali mountain sheep (Ovis ammon polii) by genotyping 9 neutral and 8 candidate gene microsatellite loci in 172 individuals noninvasively sampled across five study areas in Afghanistan, China, and Tajikistan. Heterozygosity and allelic richness were generally high (mean H = 0.67, mean A = 6.1), but were significantly lower in the China study area (H = 0.61, P \ 0.001; A = 4.9, P \ 0.01). One marker in an immune system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Estimating heterozygosity is therefore important because positive correlations between heterozygosity and both fitness (FitzSimmons et al ) and resistance to disease have also been documented in bighorn sheep (Coltman et al , Luikart et al ). We found estimated heterozygosities in the RMNP herds to be comparable to the highest values reported in other studies of native bighorn sheep populations (Boyce et al , Forbes and Hogg 1999, Epps et al , Johnson et al , Luikart et al ) and higher than those reported for some restored bighorn sheep populations (Whitaker et al , Olson et al ). Our inbreeding coefficient estimates support these heterozygosity estimates in that we did not detect a significant loss of heterozygosity, as indicated by a large positive F is .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Estimating heterozygosity is therefore important because positive correlations between heterozygosity and both fitness (FitzSimmons et al ) and resistance to disease have also been documented in bighorn sheep (Coltman et al , Luikart et al ). We found estimated heterozygosities in the RMNP herds to be comparable to the highest values reported in other studies of native bighorn sheep populations (Boyce et al , Forbes and Hogg 1999, Epps et al , Johnson et al , Luikart et al ) and higher than those reported for some restored bighorn sheep populations (Whitaker et al , Olson et al ). Our inbreeding coefficient estimates support these heterozygosity estimates in that we did not detect a significant loss of heterozygosity, as indicated by a large positive F is .…”
Section: Discussionsupporting
confidence: 87%
“…Each run included 10,000 iterations and we evaluated the data under 7 different model parameter combinations: TPM with 5% IAM and variance of 12, TPM with 5% IAM and variance of 30, TPM with 10% IAM and variance of 12, TPM with 10% IAM and variance of 30, TPM with 20% IAM and variance of 12, TPM with 20% IAM and variance of 30, and a strict SMM model. We selected these parameter combinations based on author recommendations (Piry and Cornuet 1999) and previous work on bighorn sheep (Ramey , Ramey et al , Luikart et al ). We evaluated allele frequency distributions graphically via a qualitative mode‐shift indicator of bottlenecked populations identified by a disproportionate loss of rare alleles.…”
Section: Methodsmentioning
confidence: 99%
“…Three of the 16 markers used in the Rousset's a calculations were excluded from the expected heterozygosity estimation, because these markers were suspected to be linked with potentially adaptive alleles [43][44][45]. Although these three loci were shown to behave neutrally 37,46,47 we chose to exclude these markers from the expected heterozygosity analysis to avoid any cryptic selective influences on heterozygosity metrics. Heterozygosity estimates using a similar number of microsatellite loci have been shown to correlate with population isolation 35 , elevation 34 , and NDVI 32 in the Mojave Desert bighorn sheep metapopulation.…”
Section: Sample Collection Andmentioning
confidence: 99%
“…Because some segment of the population may be moving through the study area in fall and winter, and surveys are not conducted during the same dates every year, differences in abundance among years may be obtained. Genetic evidence and direct observations indicate connectivity between the Marco Polo sheep populations of Afghanistan and Tajikistan (Luikart et al 2011, Rosen 2012. Large numbers of wild sheep are known to occur adjacent to our study area in Tajikistan.…”
Section: Discussion Abundancementioning
confidence: 99%